Double inversion recovery MRI versus contrast-enhanced MRI for evaluation of knee synovitis in juvenile idiopathic arthritis - Floris Verkuil; Robert Hemke; E. Charlotte van Gulik; Anouk M. Barendregt; Amara Nassar-Sheikh Rashid; Dieneke Schonenberg-Meinema; Koert M. Dolman; Eline E. Deurloo; Kees F. van Dijke; J. Michiel den Harder; Taco W. Kuijpers; J. Merlijn van den Berg; et al. (Insights into Imaging, 2022)
Abstract Background Double inversion recovery (DIR) MRI has the potential to accentuate the synovium without using contrast agents, as it allows simultaneous signal suppression of fluid and fat. The purpose of this study was (1) to compare DIR MRI to conventional contrast-enhanced (CE) MRI for delineation of the synovium in the knee in children with juvenile idiopathic arthritis (JIA) and (2) to assess the agreement between DIR MRI and CE-MRI regarding maximal synovial thickness measurements. Results In this prospective study, 26 children with JIA who consecutively underwent 3.0-T knee MRI between January 2018 and January 2021 were included (presence of knee arthritis: 13 [50%]; median age: 14 years [interquartile range [IQR]: 11–17]; 14 girls). Median confidence to depict the synovium (0–100 mm visual analogue scale; scored by 2 readers [consensus based]) was 88 (IQR: 79–97) for DIR MRI versus 100 (IQR: 100–100) for CE-MRI (p value = < .001). Maximal synovial thickness per child (millimeters; scored by 4 individual readers) on DIR MRI was greater (p value = < .001) in the children with knee arthritis (2.4 mm [IQR: 2.1–3.1]) than in those without knee arthritis (1.4 mm [IQR: 1.0–1.6]). Good inter-technique agreement for maximal synovial thickness per child was observed (r s = 0.93 [p value = < .001]; inter-reader reliability: ICC DIR MRI = 0.87 [p value = < .001], ICC CE-MRI = 0.90 [p value = < .001]). Conclusion DIR MRI adequately delineated the synovium in the knee of children with JIA and enabled synovial thickness measurement similar to that of CE-MRI. Our results demonstrate that DIR MRI should be considered as a child-friendly alternative to CE-MRI for evaluation of synovitis in children with (suspected) JIA.